WATERMARKING AND ANALYSING DIGITAL IMAGE APPLICATION. - Ya Abdullah, Norhaiza; Wan Hassan, Siti Wan Mazidah; Mohd Husny, Herny Ramadhani; Wan Ismail, Wan Hazimah (Journal of Computing Technologies and Creative Content, 2017)
Uploading and sharing pictures on Internet seems to be common things to do nowadays and these pictures eventually will be downloaded back or repeatedly sharing among the user making the pictures less secure and easier to be manipulated for other purpose. One of the ways to protect these pictures is by using watermark. Watermark is capable of carrying information as authentication or authorization codes, or a legend essential for image interpretation. The capability is envisaged to find application in image tagging, copyright enforcement, counterfeit protection and controlled access. Nevertheless, by embedding the watermark itself is not going to strengthen the security, thus the ability to analyse the modified pictures are well demanded. By analysing the pictures, it can verify the content and detect the differences between two images or in other context; which are original digital image and modified digital image. Therefore, a system is proposed to combine both watermark and analysing ability features in one system to enhance security to the pictures. We conducted analysis on digital image from various format of image’s metadata. It is hope that the proposed combination methods can be one of the method to ensure digital image is more secure and reliable.